Sosialisasi Perlindungan Perempuan Dan Kekerasan Dalam Rumah Tangga (KDRT) Kelurahan Batu X Di Tanjungpinang Timur, Provinsi Kepulauan Riau - Sri Wahyuni; Emi Solina; Zaitun Zaitun; Hendra Hendra; Taufik Taufik (Universitas Pahlawan Tuanku Tambusai, 2021)
The purpose of PKM activities is to provide education to the public regarding the Protection of Women and Domestic Violence (KDRT) Batu X Village in East Tanjungpinang, Riau Islands Province due to the issue of violence against women in their position as daughters, wives, members of a community both physically and psychologically. nowadays it is increasingly happening in society, sometimes it is considered commonplace and is not resolved in the realm of state law. In particular, in a household bond, it shows that domestic violence against the wife, this is certainly inseparable from the social construction that develops in society that the husband is the husband. a man who is considered superior, is the leader and head of the family, has full authority over his family, including his wife. The method of this activity is socialization in the form of lectures, discussions and questions and answers. The result of this activity is that it is necessary to carry out continuous education for the community on the protection of women and domestic violence (KDRT).